Does knee extensors and flexors muscle strength and strength balance differ by playing position of soccer players? - Misjuk, M.; Rannama, I.; Zusa, A. (LASE Journal of Sport Science, 2019)
The purpose of this study is to compare the strength and muscle balance of peak torque of knee extensors and flexors of soccer players according to playing positions. The strength parameters consist of absolute and relative strength, and muscle balance parameters of bilateral strength balance and H/Q ratio of dominant and non-dominant leg. The participants of this study are 102 male soccer players of Estonian Premium League teams: 41 defenders, 40 midfielders and 21 forwards. Muscle strength is measured in the isokinetic concentric mode at angular velocities of 60 and 300°/s and in the eccentric mode at 60°/s (Humac Norms). The one-way ANOVA and Bonferroni methods are used to compare strength parameters between positions.The Student t-test is used to compare dominant and non-dominant leg within the playing position groups. We find that absolute peak torque values of midfielders are statistically significantly smaller than defenders and forwards at angular velocity 60°/s on concentric and eccentric mode. No statistically significant differences are found between soccer players' positions at angular speed 300°/s. We find that relative peak torque does not differ statistically significantly between players position. Defendershave statistically significantly stronger dominant leg compared to non-dominant leg in the concentric and eccentric mode at angular velocity 60°/s. No statistically significant differences are found between playing positions in bilateral strength balance and H/Q ratio. Players in different playing position have different knee extensors and flexors strength values, but no differences are observed between playing position and knee extensors and flexors strength balance.